Meningkatkan Hasil Belajar PAKBP Melalui Model Pembelajaran Problem Based Learning Materi Sengsara dan Wafat Yesus dengan Bantuan Media Video Kelas VIII FASE D SMP Negeri 1 Sorkam - Dewi Susanti Tarigan; Yusmanto Yusmanto; Busri Busri (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to determine the increase in learning outcomes using the Problem Based Learning learning model on the learning outcomes of class VIII Phase D students in the subject of Catholic Religious Education. This research was conducted at SMP Negeri 1 Sorkam. With a total of 31 students. Classroom action research is a scientific activity carried out by teachers in the classroom using actions to improve the quality of learning. So, classroom action research is very important for teachers to carry out, because solving existing educational problems will help improve the quality of education in Indonesia. Therefore, researchers will discuss how important it is to carry out classroom action research.